Isolation of the spirochaete Borrelia afzelii from the mosquito Aedes vexans in the Czech Republic - Halouzka, J; Postic, D; Hubálek, Z (Medical and veterinary entomology, 1998)
During the years 1993-1995, a total of 3580 culicine mosquitoes of six species were collected in South Moravia, Czech Republic, and examined by dark-field microscopy for the presence of borreliae. Females of Aedes cantans, Ae. sticticus, Ae. vexans, Culex pipiens and Cx pipiens biotype molestus (but not Ae. geniculatus or Culiseta annulata) harboured spirochaetes, the frequencies ranging from 0.7% to 7.8%. One isolate (BR-53) from Ae. vexans was identified as Borrelia afzelii genospecies. The potential role of mosquitoes in the epidemiology of Lyme borreliosis should be investigated.
Keywords: Česká republika; Czech Republic; Insect Vectors; Borrelia; lymeská nemoc; Animals; lidé; Aedes; hmyz - vektory; Host-Parasite Interactions; Humans; zvířata; interakce hostitele a parazita; Lyme Disease